Revealing Annemarie Schimmel's Interpretation of The Sufi Texts Through Gadamer's Philosophical Hermeneutic Analysis - Muhammad Hisyam Syafii; Ahmad Hermawan; Husain Azhari; Lala Afafa (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This study presents common problems of Sufi texts’ interpretation by orientalists, with a specific emphasis on the Annemarie Schimmel’s works. The primary purpose of this study is to uncover biases and limitations that may reside in Schimmel's approach to Sufism and to pave the way for a more reflective and contextual approach in Islamic studies. This work employs a philosophical hermeneutic approach developed by Hans-Georg Gadamer. The primary data source comes from Schimmel's works on Sufism, while secondary data are obtained from academic literature related to hermeneutics, Orientalism, and the study of Sufism. The results of the study show that Schimmel's understanding of Sufi texts is influenced by her prejudices and understandings as an orientalist. Schimmel's "casting fusion" process produces a rich interpretation but is not free from inherent bias. In conclusion, this study has revealed essential dimensions in the hermeneutics of Sufi texts studied by Schimmel and the emphasis on the need for more critical and reflective cross-cultural dialogue to understand the Islamic spiritual tradition more deeply.